(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the attitude formed by the legal philosophy of the state as a part of the normative foundations of the life of the society is studied. Such relations are the result of the implementation of norms of various accepted associations. It is based on the influence of legal thinking on social relations such as “free law” and “institution of social control”.